Claiming collectivity: the socio-political affects of hashtagging "us". Issue 2 (15th March 2023) - Fitzpatrick, Claire
ABSTRACT: This article explores the role that hashtags play in maintaining the prevailing socio-political underpinnings of inequality. It is written in response to the 2019 terror attacks on Muslim communities in Ōtautahi, Christchurch. The attacks called into question many previously held assumptions about the non-discriminatory nature of Aotearoa New Zealand politics and society, necessitating a greater attentiveness to the grounds upon which claims to solidarity are made. I argue that "collectivizing hashtags" – that is, social media hashtags characterized by their use of pronouns to inclusively identify with Others – afford new opportunities for self-expression that may simultaneously empower and compromise certain individuals. I demonstrate how the collectivizing hashtags #TheyAreUs and #ThisIsNotUs involve forms of appropriation on the part of privileged subjects, reinforcing unequal social hierarchies and silencing marginal subjects. Following the feminist traditions of Judith Butler, Erinn Gilson, and Kate Schick, my analysis incorporates an ethic of vulnerability to interrogate underlying power relations and our location within them. This analysis encourages people to think critically about assuming the identity of vulnerable Others; otherwise, we risk obscuring our own complicity in the wider relations of power in which discrimination, oppression, and violence fester.